A meta-analysis of the effect of small-sided games on the repeated sprint ability in soccer - Morera Siércovich, Pier Luigi (2020)
To determine the effect of small-sided games (SSG) on the repeated sprint ability (RSA) in male soccer players. A meta-analysis was conducted in which studies were selected from the electronic databases Medline, SPORTDiscus, Google Scholar, and PubMed. Results: Six studies were included and 44 effect sizes (ES) were computed from 116 men (age = 18.0 ± 2.8 yr., height = 175.8 ± 3.3 cm, weight = 68.6 ± 5.6 kg, body mass index [BMI] = 22.3 ± 1.1 kgm2, VO2max = 56.9 ± 2.1 mlkg-1min-1). The SSG training improved the overall RSA performance (ES = -.54, 95%CI = -.89, -.20, p < .05), reduced RSA total time (ES = -.41, 95%CI = -.81, -.01, p < .05), and fatigue index (ES = -.83, 95%CI = -1.65, -.02, p < 0.05). Moderator analysis showed that the fatigue index is impaired when several sessions/week are performed (β = .69, 95%CI = .29, 1.10, R2 = 82.9, p = .001) and is enhanced when the duration of the intervention is extended over several weeks (β = -.25, 95%CI = -.47, -.03, R2 = 56.6, p = .05). The methodological use of SSG enhances the capacity of repeated sprints, while technical and tactical elements are worked concomitantly.